Motives and Techniques of Creative Accounting - Lenka STRAKOVA (Communications of International Proceedings, 2021)
Creative accounting is characterized by a large number of forms, so it is difficult to detect its practices in the business environment. If the financial statements are distorted, users of the information from the financial statements will obtain false and inaccurate information, which may have a significant impact on their decisions. Units of account in a business environment, use distortions of accounting information primarily to achieve favorable economic results to present themselves in a more positive image and also to seek to attract large numbers of investors, disproportionately reduce the tax base through artificial revenue cuts or disproportionate cost increases. This paper aims to theoretically define the concept of creative accounting and point out the motives and techniques leading to the use of creative accounting. This paper also focuses on examples of companies around the world where creative accounting practices have been uncovered. To meet this goal, the paper uses the method of classification of technical terms, the method of deduction, induction, and illustrative examples.
Keywords: Financial Statement; Accounting Data; Creative Accounting; Financial Manipulation.